Redox mediated synthesis of hierarchical Bi2O3/MnO2 nanoflowers: a non-enzymatic hydrogen peroxide electrochemical sensor. Issue 11 (11th February 2016) - Ray, Chaiti; Dutta, Soumen; Roy, Anindita; Sahoo, Ramkrishna; Pal, Tarasankar
Abstract : Redox mediated synthesis of Bi2 O3 /MnO2 nanoflowers for efficient electrochemical sensing of hydrogen peroxide down to 0.05 μM. Abstract : Uniform hierarchical Bi2 O3 /MnO2 nanoflowers (BM NFs) are fabricated via a reaction strategy by combining redox reaction and hydrothermal treatment. This wet chemical method reports for the first time a one pot synthesis of Bi2 O3 /MnO2 nanoflowers via a thermodynamically allowed galvanic reaction between Bi(0) and KMnO4 in aqueous solution under modified hydrothermal (MHT) conditions. The Bi2 O3 /MnO2 NF composites are then applied as a catalyst for electrochemical hydrogen peroxide detection. Exceedingly high H2 O2 detection sensitivity (0.914 μA μM −1 cm −2 ) lies in a wide linear range of 0.2–290 μM and the detection limit goes down to 0.05 μM (S/N = 3) for non-enzymatic detection of H2 O2 in solution. This prototype sensor demonstrates an admirable analytical performance considering its long-term stability, good reproducibility and acceptable selectivity against common interfering species. The employment of the stable nanocomposite for real sample analysis makes it a deliverable for H2 O2 sensing.